Mechanisms of Autoantibody Production in Systemic Lupus Erythematosus - Han, Shuhong; Zhuang, Haoyang; Shumyak, Stepan; Yang, Lijun; Reeves, Westley H. (Frontiers in Immunology, 2015)
Autoantibodies against a panoply of self-antigens are seen in SLE, but only a few (anti-Sm/RNP, anti-Ro/La, anti-dsDNA) are common. The common lupus autoantigens are nucleic-acid complexes and levels of autoantibodies can be extraordinarily high. We explore why that is the case. Lupus is associated with impaired central or peripheral B cell tolerance and increased circulating autoreactive B cells. However, terminal differentiation is necessary for autoantibody production. Nucleic acid components of the major lupus autoantigens are immunostimulatory ligands for TLR7 or TLR9 that promote plasma cell differentiation. We show that the levels of autoantibodies against the U1A protein (part of a ribonucleoprotein) are markedly higher than autoantibodies against other antigens, including dsDNA and the non-nucleic acid-associated autoantigens insulin and thyroglobulin. In addition to driving autoantibody production, TLR7 engagement is likely to contribute to the pathogenesis of inflammatory disease in lupus.